FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR - NATASHA SHERINA CANDRA; MOHAMMAD EDDY ROSYADI (E-Jurnal Akuntansi TSM, 2021)
The objective of this research is to obtain empirical evidence about the influence of leverage, firm size, board size, auditor size, managerial ownership, financial performance, operating cash flow, audit tenure, and corporate social responsibility to earning management in Indonesia manufacturing companies. This research also wants to explore the direction of influence independent variables given to dependent variable. This research obtains the sample from Indonesia manufacturing companies listed in Indonesia Stock Exchange from 2017 until 2019. The sampling method used in this research is purposive sampling method and there are 35 companies with 105 data meet the criteria. This research uses multiple regression method for data analysis. The result shows that financial performance and operating cash flow have influence on earning management. On the other hand, leverage, firm size, board size, auditor size, managerial ownership, audit tenure, and corporate social responsibility have no influence on earning management